2019
DOI: 10.4315/0362-028x.jfp-18-349
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Quality and Safety of Sushi Prepared with Gloved or Bare Hands: Food Handlers' Impact on Retail Food Hygiene and Safety

Abstract: Food handlers play an important role in retail food hygiene and safety. This study was conducted to better understand the impact of food handlers on the microbiological quality and safety of sushi and ingredients handled by gloved and bare hands. At retail premises, food handlers were asked to prepare a batch of sushi with raw fish followed by a batch of sushi with cooked ingredients. Food (sushi and ready-to-eat ingredients), hand, and glove samples were collected for analysis of overall microorganisms (stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
12
0
4
Order By: Relevance
“…Handling ready-to-eat foods with bare hands can result in cross-contamination of foods by pathogens present on food handlers' hands (175). An FDA report (159) on food service risk factors stated "preventing bare hand contact with ready-to-eat foods is a major control measure for limiting the spread of harmful bacteria and viruses from the hands to ready-to-eat food."…”
Section: Fda Model Food Code and Hand Washingmentioning
confidence: 99%
See 2 more Smart Citations
“…Handling ready-to-eat foods with bare hands can result in cross-contamination of foods by pathogens present on food handlers' hands (175). An FDA report (159) on food service risk factors stated "preventing bare hand contact with ready-to-eat foods is a major control measure for limiting the spread of harmful bacteria and viruses from the hands to ready-to-eat food."…”
Section: Fda Model Food Code and Hand Washingmentioning
confidence: 99%
“…¶ (H) Before donning gloves to initiate a task that involves working with food. The hands of food workers can become contaminated with pathogens by handling contaminated raw food, dirty surfaces, or themselves during a variety of activities (66,106,133,165,175). In a laboratory-based study where hands were artificially contaminated with a foodborne pathogen surrogate, washing hands before donning gloves significantly reduced contamination of the outside of the gloves and reduced contamination of food subsequently handled with gloved hands (122).…”
Section: Fda Model Food Code and Hand Washingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a pathogenic microorganism can remain viable in cutting boards and food contact surfaces [6][7][8] demanding the rigorous cleaning and disinfection of kitchen utensils, equipment and surfaces [9,10]. Hands of food handlers have also been considered an important determinant of microbiological contamination of food and washing hands plays a valuable role in preventing the transmission of foodborne illnesses [4,11,12]. Staphylococcus aureus colonizes the nasopharynx of asymptomatic carriers leading to the contamination of the hands of food handlers [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the Annual Communicable Diseases Surveillance report published by the Ministry of Health (Communicable Diseases Surveillance report 2018) in Singapore documented 398 notifications of food poisoning involving 3165 cases in 2018 and B. cereus was among the top three suspects of the reported outbreaks. Several other investigations demonstrated that B. cereus contamination can arise after improper handling of food and raw vegetables, poor hygienic practices of food handlers, and also from polluted environments, including the air [17][18][19].…”
Section: Introductionmentioning
confidence: 99%